Tislelizumab versus sorafenib as first-line treatment for advanced hepatocellular carcinoma in China: a cost-effectiveness analysis - Zheng, Zhiwei; Lin, Yuxuan; Cai, Hongfu (Frontiers in Public Health, 2024)
Objective The goal of this study is to compare the cost-effectiveness of tislelizumab and sorafenib as first-line treatment for advanced hepatocellular carcinoma in China. Methods A comprehensive cost-effectiveness analysis was undertaken within the framework of a partitioned survival model to accurately gage the incremental cost-effectiveness ratio (ICER) of tislelizumab compared to sorafenib. The model incorporated relevant clinical data and all survival rates were from RATIONALE-301 trials. The stability of the partitioned survival model was assessed by performing one-way and two-way sensitivity analyses. Results The total cost incurred for the tislelizumab treatment was 16181.24, whereas the sorafenib was 14306.87. The tislelizumab regimen resulted in a significant increase of 0.18 quality-adjusted life years (QALYs) and an extra cost of 1874.37 as compared to chemotherapy. The ICER was 10413.17 per QALY, which was found to be below the willingness-to-pay (WTP) threshold of 37304.34/QALY. The results of the sensitivity analysis found that no fluctuations in any of the factors affected our results, even when these parameters fluctuated. Conclusion Tislelizumab appears to be a cost-effective first-line treatment for advanced hepatocellular carcinoma when compared to sorafenib in China. These findings can inform decision-making processes regarding the selection of the most cost-effective treatment option for advanced hepatocellular carcinoma.